info Hansen: A new online resource for Hansen’s disease - Deps, Patrícia (PLoS neglected tropical diseases, 2020)
The aim of info Hansen is to provide an educational resource created and hosted in Brazil, combining content provided by Brazilian and international contributors on a wide range of topics, that is then disseminated to national and international healthcare professionals, researchers, academics, persons affected by Hansen’s disease, and the public, in Portuguese, Spanish, French, and English. info Hansen arose from an initiative to engage medical students in Brazil with the subject of a disease that remains endemic in their country and that therefore creates a need for newly qualified physicians to have clinical, psychosocial, and historical knowledge that they can use should they encounter Hansen’s disease in their future practice. The site will provide free access to a Hansen’s disease in Clinical Practice e-book comprising chapters written by subject matter experts on every aspect of Hansen’s disease, including its history, epidemiology, immunology, environmental sources, clinical manifestations, diagnosis, and treatment. The Committee to Assist Brazilian Immigrants Afflicted by Hansen’s disease (CAIBAH) will be an electronic sister resource to info Hansen, providing information for immigrants affected by Hansen’s disease who encounter difficulties and prejudice in their new home countries. info Hansen seeks to address the imbalance in information being generated and shared from countries that carry the burden of Hansen’s disease, because Brazil is rich in knowledge, expertise, and human resources.